Targeted analysis of KRAS and CREBBP mutations uncovers a potential population-specific signature in thai patients with liver fluke-associated cholangiocarcinoma - Rehab Osman Taha; Wanna Chaijaroenkul; Papichaya Phompradit; Kesara Na-Bangchang (PLoS ONE, 2026)
Intrahepatic cholangiocarcinoma (iCCA) is an aggressive malignancy with limited therapeutic options and a poor prognosis. Opisthorchis viverrini (OV) infection is a major risk factor in endemic regions, particularly in Southeast Asia. However, the molecular mechanisms underlying iCCA development and progression remain incompletely understood. This study, as it is, is observational and demonstrates association rather than causation. This study aimed to characterize genetic alterations in key germline variants associated with cancer risk and prognosis, as well as components of the oxidative stress pathway, and to evaluate their associations with clinicopathological features in Thai iCCA patients. A cohort study was conducted involving 112 iCCA patients, 60 OV-infected individuals, and 156 healthy controls. Genetic alterations in TP53 , CREBBP , KRAS (codons 12 and 13), CDKN2A , IDH1 , and GZMB were analyzed by PCR and sequencing. Gene polymorphic co-occurrence and burden were assessed. Additionally, polymorphisms in the KEAP1–NFE2L2 oxidative stress pathway ( KEAP 1 rs11085735 ; NFE2L2 rs6726395 , rs6721961 , rs4893819 ) were analyzed in 50 iCCA patients. Associations with clinicopathological parameters, including metastatic status, tumor size, and tumor markers (CEA and CA 19−9), were evaluated using odds ratios (OR) and statistical analyses. CREBBP polymorphisms were significantly more frequent in iCCA patients (50.0%) than in OV-infected individuals (30.0%) and healthy controls (30.8%) (P = 0.003), with homozygous mutations conferring the highest cancer risk (OR = 6.43, 95% CI: 1.70–24.31). KRAS codon 13 polymorphisms were detected exclusively in iCCA patients (21.4%) and were absent in OV-infected individuals. In contrast, TP53 polymorphisms were highly prevalent across all groups, with no significant differences, suggesting these variants may represent background genetic variation rather than tumor-specific drivers . Co-polymorphism analysis revealed that TP53 and CREBBP alterations were the dominant genetic events, with most tumors harboring one or two mutations (mean gene polymorphism burden: 1.46 ± 0.86). Further statistical modeling revealed significant clinicopathological associations. Binary logistic regression identified tumor size (P = 0.029) and TP53 mutation status (P = 0.037) as significant predictors of metastasis. Notably, TP53 wild-type status demonstrated a protective effect against metastasis (OR = 0.083, 95% CI: 0.007–0.950, P = 0.045), and multivariable analysis confirmed TP53 as an independent predictor of metastasis (P = 0.037) after adjusting for sex, age, and sex-by-age interaction. Furthermore, ordinal regression identified metastasis as the primary predictor of advancing tumor stage (P < 0.001), with tumor size showing a trending association (P = 0.068). Evaluation of CDKN2A was limited by quasi-complete separation (adjusted OR = 0.000, P = 1.000) due to sample size constraints. Analysis of the KEAP1–NFE2L2 pathway revealed limited genetic diversity in KEAP1 but substantial polymorphic variation in NFE2L2 . These polymorphisms showed minimal associations with clinicopathological features, suggesting a complex role of oxidative stress regulation in iCCA pathogenesis. The study identifies CREBBP and KRAS codon 13 polymorphisms as key genetic alterations enriched in iCCA, supporting their role as candidate germline variants and potential therapeutic targets. Polymorphism co-occurrence patterns indicate a relatively low mutational burden, with epigenetic dysregulation and oncogenic signaling representing central mechanisms in iCCA development. Further large-scale studies integrating tissue and circulating DNA analyses are warranted to validate these findings and identify clinically actionable biomarkers in iCCA.